PENERAPAN NILAI-NILAI PENDIDIKAN ISLAM DALAM METODE MARIA MONTESSORI DI BRAINY BUNCH INTERNATIONAL ISLAMIC MONTESSORI SCHOOL - Fatihatul Muthmainah (EL-TARBAWI, 2017)
Montessori method is a method which makes children the central of the educational process, and teachers become directors, the guide, without much intervention, independent learning activities of children. The focus of this paper is how Islamic education can be combined with Western methods. This research used a qualitative approach. The subject in this study was determined with purposive sampling. Data collection in this study used the method of observation, interviews, and field note. The results of this research show that the reason for using Montessori method is because this method does not classify the children based on their age. The application of discipline at Brainy Bunch International Islamic School uses ground rules and the sunnah. Islamic education values are applied in the Brainy Bunch through Islamic subjects and Brainy Bunch’s statement: to produce a dynamic Muslims who practices the teachings of Al-Quran and Hadeeth as their true guidance in life, and teachers who are English proficient and trained in the Montessori method of teaching as the output of this school. Keywords: Islamic educational values, Montessori method